AMINO-ACID-VITAMIN AND MINERAL COMPLEXES IN NOURISHMENT OF SICKLY CHILDREN - Zh.Yu. Gorelova; T.B. Sentsova; A.N. A.N. Plats-Koldobenko ("Paediatrician" Publishers LLC, 2006)
(Voprosy sovremennoi pediatrii = Current pediatrics. 2006;5(5):105)